Optimization of Straight Movement 6 Dof Robot Arm With Genetic Algorithm - R Suryoto Edy Raharjo; Oyas Wahyunggoro; Priyatmadi . (Proceeding of the Electrical Engineering Computer Science and Informatics, 2014)
This paper proposes a genetic algorithm (GA) to optimize the straight movement of the robot arm for 6 DOF. The objective function of the GA is proposed to find the optimal values of the movement of the robot arm in a straight line trajectory. As more and more levels of Degree of Freedom (DoF), the more difficult to achieve precision, especially during straight motion from the starting point (initial point) to the point of destination (final point), which is affected by the determination of the swivel angle of each actuator, the linearity of the trajectory length straight-effector motion, and the number of Intermediate Point required. Forward kinematics is used to find the coordinates of the end effector, and a linear function of a straight line from the starting point (initial point) to the point of destination (final point) is used as the objective function of GA.